Density, Viscosity and Speed of Sound for Benzaldehyde with Isopropylbenzene System at 298.15, 303.15, 308.15, 313.15 K - Kapoor, Seema; Katyal, R.C.; Kaur, Jasmeet; Chugh, Deepali (Asian Journal of Chemistry, 2010)
The densities, viscosities and speeds of sound for binary mixture of benzaldehyde with isopropylbenzene at 298.15, 303.15, 308.15 and 313.15 K have been measured over the whole compositional range. The excess thermodynamic properties such as excess volume (VE), deviations in viscosity (Δη) and excess isentropic compressibility (KES ) are calculated. All of the excess properties have been fitted to Redlich-Kister equation.